The Influence of Administrative Costs, Profit Sharing and Pick Up Services on Customer Decisions to Choose Tadhabur Saving Products (Study at BPRS Lantabur Tebuireng, Lamongan Branch) - Vera Ayu Mandasari; Nasrulloh Nasrulloh (Jurnal Ilmu Ekonomi Terapan, 2023)
Financial institutions in Indonesia, both conventional and sharia, have led to increasingly fierce competition both in terms of improving service quality, providing facilities and products offered. One of the sharia financial institutions in Lamongan is BPRS Lantabur Tebuireng. This research is a quantitative study, the population in the study was 200 customers of tadhabur savings and the sample used was 67 customers using the Slovin formula. The data analysis method uses SPSS Statistics 26. The results of this study show that simultaneously, the variables of administrative costs, profit sharing and pick-up services have a significant effect on the customer's decision to choose a tadhabur savings product. Partially, administrative costs affect the customer's decision to choose a tadhabur savings product. Profit sharing (X2) affects the customer's decision (Y) to choose a tadhabur savings product and ball pick-up services affect the customer's decision to choose a tadhabur savings product.